KEPUASAN MAHASISWA DALAM MENTORING PENYUSUNAN PROPOSAL KARYA TULIS ILMIAH DI PROGRAM STUDI DIPLOMA III KEPERAWATAN POLTEKKES KEMENKES PONTIANAK - Hieronimous Amandus; Dian Mawarni; Christantie Effendy; Mubasysyir Hasanbasri (Berita Kedokteran Masyarakat (BKM), 2018)
“Difficult to meet supervisor” and “lack of feedbacks”: student’s perception of problems in writing final year project in undergraduate program Objective: This study explores the role of mentoring felt by the students involved in the making. Specifically, we want to disclose what students consider helpful and what is considered to be less helpful for final project preparation. Methods: Respondents were 82 third year nursing students at Poltekkes Kemenkes Pontianak who were writing thesis. The questionnaire consisted of 16 questions consisting of (a) lecturer-student communication and interaction, (b) mentoring roles and responsibilities, and (c) quality of mentorship. The questionnaire consisted of a question following the items in Beck et al.’s research, measured by a Likert scale consisting of good, moderate, and less. Six students were taken for in-depth interviews, selected based on different counselors. Results: Of the 16 themes about mentoring, “pretty good” at most for all items. Item analysis showed support of several concerns that have been predicted. Although “like the guiding figure” and “feel the support of lecturers including two things that stand out in the opinion of students about thesis supervisor figure. Students reported two main issues in their mentoring process: “advisers are difficult to see” and “lack of meaningful input from advisers”. Conclusion: Student satisfaction in mentoring is influenced by the quality of the mentors. Students feel satisfied if the characteristics, roles and responsibilites of the supervisor in accordance with student expectations. This study ensures that there are limitations in the availability and seriousness of the lecturers in thesis coaching. Further studies on mentorship and support capacity are needed. AbstrakTujuan: Penelitian ini mengeksplorasi peran mentoring yang dirasakan oleh mahasiswa terkait dalam pembuatan. Secara spesifik, kami ingin mengungkapkan hal-hal apa yang dianggap mahasiswa membantu dan hal seperti apa yang dianggap kurang membantu penyusunan tugas akhir. Metode: Responden adalah 82 mahasiswa keperawatan tahun ketiga di Poltekkes Kemenkes Pontianak yang sedang menulis skripsi. Kuesioner terdiri dari 16 pertanyaan yang terdiri dari (a) komunikasi dan interaksi dosen-mahasiswa, (b) peran dan tanggung jawab pembimbingan, dan (c) kualitas pembimbingan. Kuesioner terdiri dari pertanyaan mengikuti item dalam penelitian Beck et al., diukur dengan skala Likert terdiri dari baik, cukup, dan kurang. Enam mahasiswa diambil untuk wawancara mendalam, dipilih berdasarkan pembimbing yang berbeda. Hasil: Dari 16 tema tentang pembimbingan, “cukup baik” paling banyak untuk semua item. Analisis perbandingan antar item membuktikan kekhawatiran yang sering mengemuka. Meskipun “menyukai sosok pembimbing” dan “merasa mendapat dukungan dari dosen termasuk dua hal yang menonjol dalam pendapat mahasiswa tentang sosok pembimbing skripsi. Penelitian ini melaporkan dua hal yang paling mencolok terkait dengan proses pembimbingan: dosen tidak mudah ditemui dan mahasiswa tidak merasa mendapat masukan yang berarti dalam proses belajar. Simpulan: Studi ini mengukuhkan keterbatasan dalam kapasitas dari dosen dalam pembimbingan skripsi. Studi lebih lanjut tentang kapasitas pembimbing dan dukungan untuk mereka sangat mendesak.